From the shadows to light. Perceptions of women and healthcare providers of post-abortion care in Burkina Faso. (September 2020) - Ouedraogo, Ramatou; Juma, Kenneth
Abstract: Despite political commitments to address maternal deaths due to abortion, women and girls in Burkina Faso still face impediments to accessing post-abortion care (PAC) services, including stigma, high costs, and negative patient-provider relationships. Based on a three-year ethnographic study in Ouagadougou, Burkina Faso (2011–2014), this paper provides an in-depth examination of the experiences and perceptions of patients and healthcare providers when seeking or delivering PAC. Extensive participant observation of PAC service delivery was carried out in five primary and three referral health facilities, as well as in-depth interviews with 13 healthcare providers and 39 patients. Data were analyzed using a thematic analysis approach and discussed using relevant literature. Patients and providers conceptualized PAC as literally "womb washing'', vividly reflecting on the realities around health risks of abortion, procreation and role of health providers. Moreover, women described PAC as a life-saving intervention capable of averting infections and other complications, but also bears significant risks of disclosure depending on the uterine evacuation technology used (manual vacuum aspiration versus medical abortion). In delivering PAC services, healthcare providers agonize over the dilemmas they face, mainly derived from their conceptualization of PAC services and how they cope with discomfort using PAC technology options. Our findings present the intersection between patients' and providers' conceptions of PAC, and how these perceptions drive the choice of technology for uterine evacuation to mitigate stigma. We argue that these perceptions drive patient and healthcare provider practices around decision making to seek or deliver care, and patient-provider interactions in health facilities. These findings offer important guidance for interventions seeking to improve access and quality of PAC. Highlights: Analyses views of healthcare providers and post-abortion patients in Burkina Faso. Shows how women navigate PAC service access in a legally-restrictive context. Explains how care providers and patients cope with abortion-related stigma. Illustrates how PAC technologies can mitigate or worsen obstetric violence.